PENGARUH KEMAMPUAN KERJA, PENGEMBANGAN KARIR DAN KOMUNIKASI TERHADAP KEPUASAN KERJA PEGAWAI PADA BIDANG KEUANGAN DINAS PENDIDIKAN, PEMUDA DAN OLAHRAGA KABUPATEN BIREUEN - Tasrief, Tasrief; Fauzi, Fauzi (LPPM-UNIKI, 2021)
This study aims to analyze the effect of 1). The work ability of employees in the financial sector on job satisfaction, 2). Career development of employees in the financial sector on job satisfaction, 3). Communication between employees and leaders in the financial sector on job satisfaction, 4). Employee work ability, career development and communication of employees in the financial sector on job satisfaction at the Office of Education, Youth and Sports, Bireuen Regency. The research was conducted quantitatively with a descriptive study and verification using path analysis. The results of the study concluded that simultaneously the factors of employee work ability, career development, and employee communication in the Finance Department of the Education, Youth and Sports Office of Bireuen Regency had an effect on employee job satisfaction. Partially, it is obtained that a). It is statistically proven that the work ability of employees has an effect on job satisfaction. With a large influence of 10.61 percent. b) It is statistically proven that career development factors affect job satisfaction of the employees of the Education, Youth and Sports Office of Bireuen Regency. The magnitude of the effect is 11.21 percent, and c). It is statistically proven that career development factors affect employee job satisfaction, the magnitude of the effect is 40.39 percent. The contribution of work ability, career development and communication factors to employee job satisfaction, amounted to 62.10%. This is evidenced by the following path fit model: Y = 0.188 X1 + 0.203 X2 + 0.547 X3